Urban Farming dalam Meningkatkan Ketahanan Pangan Masyarakat Perkotaan - I Dewa Gede Putra Sedana; Ni Luh Putu Ening Permini (Universitas Katolik Widya Karya Malang, 2023)
Urban farming has so far been initiated by various actors including: the government, the private sector, and community groups. In this study it is useful to find out the analysis in looking at the implementation of urban farming in Denpasar City. This study discusses the differences in the role of urban farming between city government programs and independent organizations, in terms of resources as well as through policy failures and market failures through a qualitative approach. The failure of the policy was due to the agricultural policy initiated by the City Government being less successful in meeting the food needs of the people. Therefore innovation is needed through top down urban farming. Meanwhile, market failure occurred in urban farming in the city of Bandung due to people's discomfort with the products circulating in the market. This is one of the dominant motives for the emergence of bottom-up urban farming by independent organizational groups. Meanwhile, the sources of capital for urban farming are in the form of supporting facilities for planting facilities, hydroponic installations, and making greenhouses, but the capital for urban farming formed by independent organizations comes from contributions from members of the cooperative community and bank funds. An important aspect needed by independent organizational groups is to streamline operational costs by knowing how to reuse used goods into productive goods.